Metal material with continuous net-shaped heat conduction structure and preparation method of metal material
Through the premixed powder and preplated powder stir casting process, a continuous mesh thermal conductivity structure of metal materials is constructed, which solves the problem of insufficient thermal conductivity of existing metal materials, and realizes the preparation of metal heat management materials with ultra-high thermal conductivity, maintains the simplicity and low cost of the process.
Patent Information
- Application Number
- CN202411635189.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
AI Technical Summary
The thermal conductivity of existing metal materials is insufficient, making it difficult to meet the high-speed and low-cost competition and development needs of electronic components in the intelligent era, especially in building a continuous mesh thermal conductivity structure.
Through the premixed powder and preplated powder stir casting process, the carbon-type reinforced phase is premixed and prepended to form a continuous mesh thermal conductivity structure to ensure continuous and efficient conduction of heat flow along the characteristic direction of the reinforced phase.
The thermal conductivity of metal materials has been improved, and the second generation of metal thermal management materials with ultra-high thermal conductivity has been prepared, which solves the problem that it is difficult to build a continuous mesh thermal structure in conventional stir-casting processes, while maintaining the simplicity and low cost of the process.
Smart Images

Figure CN119506633A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high thermal conductivity metal materials, and relates to a metal material with a continuous mesh thermal conductive structure and a preparation method thereof, and is suitable for preparing a metal material with an ultra-high thermal conductivity coefficient. Background Art
[0002] In the current era of rapid development of intelligent technology, the improvement of the thermal conductivity of metal materials is crucial for the development of high-power density, highly integrated and miniaturized electronic components. However, the first-generation metal thermal management materials based on matrix purification can no longer meet the increasingly stringent heat dissipation needs of electronic components. In recent years, the introduction of the second-generation metal thermal management materials has provided a powerful strategy for further optimizing the thermal conductivity of metal materials. By introducing a high thermal conductivity enhancement phase, the thermal conductivity of the base metal material can be further improved.
[0003] Stir casting is the oldest and most dynamic liquid metallurgical process in the field of metal-based materials. Its principle is to use the shear force generated by high-speed stirring blades to introduce reinforcement phases into the metal melt. The stirring casting process is highly flexible, low-cost, can form complex parts in one go, and is suitable for mass production. It plays an important role in the industrial field. At present, the stirring casting process is mainly used to introduce high-strength and high-modulus reinforcement phases (such as SiC, Ti) and distribute them randomly and evenly in the metal matrix, thereby optimizing the mechanical properties of metal materials. However, for thermal conductivity, it is more advantageous to construct a continuous network structure of the reinforcement phase than a uniformly dispersed structure. This is because the continuous network reinforcement phase structure can ensure that the heat flow is continuously and efficiently conducted along the path, thereby further optimizing its thermal conductivity. In particular, for carbon reinforcement phases with significant thermal conductivity anisotropy, the continuous network structure can make the heat flow conduct along the characteristic direction of the carbon reinforcement phase, give full play to its thermal conductivity potential, and thus significantly improve the strengthening efficiency.
[0004] Therefore, designing and developing a new stirring casting process to prepare the second-generation metal thermal management materials with a continuous network thermal conductive structure is crucial to meet the high-speed, low-cost competition and development of electronic components in the intelligent era.
[0005] According to patent and literature search, the Chinese invention patent with publication number CN103820670B discloses a method for preparing a graphite particle reinforced magnesium-based composite material. Based on the stirring casting process, a magnesium-based composite material with both high thermal conductivity and high damping performance is obtained. However, this method can only achieve a random and uniform distribution of the reinforcing phase particles, and it is difficult to construct a continuous network reinforcing phase structure that is more beneficial to thermal conductivity. Similarly, the Chinese invention patent with publication number CN116970832A proposes a method for preparing a lightweight and highly thermally conductive graphite sheet reinforced magnesium-based composite material. Based on the semi-solid stirring casting process and the extrusion process, a magnesium-based composite material with good thermal conductivity is obtained. However, this method involves a secondary extrusion process, which makes it difficult to form complex parts at one time, while increasing the process cost, and the directional distribution of the reinforcing phase produced by the extrusion makes the thermal conductivity of the composite material anisotropic. The Chinese invention patent with publication number CN117867310A discloses a method for preparing ultra-high thermal conductivity diamond / graphene reinforced aluminum-based composite materials. The carbon skeleton preform is obtained by mixing-cold pressing-heating, and then pressure infiltration is performed. The diamond / graphene three-dimensional structure is conducive to the continuous transfer of heat flow, thereby improving the thermal conductivity of the composite material. However, the overall process flow of this method is complicated, the carbon skeleton formation temperature is high, the time is long, and it is difficult to form complex parts in one go. Similarly, the Chinese invention patent with publication number CN112981205B discloses a low-cost preparation method for high thermal conductivity diamond-reinforced metal-based composite materials. The diamond powder particles are connected together by high-temperature silicone oil decomposition to form a three-dimensional interconnected network-like heat conduction path, which improves the thermal conductivity of the prepared composite material. The article An emerging class of 3D GNPs&MWCNTs structure of Mg matrix composites with improved thermal conductivity (Available online 4August 2023) published in Journal of Magnesium and Alloys reported a method of preparing a type of graphene / carbon nanotube preform with a three-dimensional oriented structure by electrostatic self-assembly and directional freeze-drying, and then preparing it by pressure infiltration to improve the thermal conductivity of magnesium alloy. However, the above method is also based on the preform-pressure infiltration process. Compared with stirring casting, its process is complicated, costly, and it is difficult to achieve one-time molding of large, complex, or thin-walled parts. Summary of the invention
[0006] In view of the poor thermal conductivity of existing metal materials and the increasingly urgent need to improve thermal conductivity, and in view of the advantages and necessity of stirring casting technology in the industrial field, the purpose of the present invention is to provide a metal material with a continuous network thermal conductive structure and a preparation method thereof, which is suitable for the preparation of ultra-high thermal conductivity metal materials with a continuous network reinforced phase structure to further optimize their thermal conductivity.
[0007] Different from the existing methods, the present invention can achieve the transformation from the randomly uniformly distributed reinforcement phase structure of the traditional stirring casting process to the continuous network reinforcement phase structure through the premixed powder (i.e. premixing) and pre-powder stirring casting process. This structure can make the heat flow in the metal matrix continuously and efficiently conduct along the characteristic direction of the reinforcement phase (high thermal conductivity direction), thereby giving full play to the thermal conductivity potential of the anisotropic carbon reinforcement phase, thereby further improving the thermal conductivity performance and preparing the second-generation metal thermal management material with ultra-high thermal conductivity.
[0008] The purpose of the present invention can be achieved by the following scheme:
[0009] In a first aspect, the present invention provides a method for preparing a metal material having a continuous network thermal conductive structure, comprising the following steps:
[0010] S1, premixing at least two carbon-based reinforcement phases to form a pre-connection;
[0011] S2, laying the pre-connected carbon reinforcement phase under the base alloy and melting it;
[0012] S3, after the temperature of the melt after smelting is cooled to above the liquidus temperature of the matrix alloy, stirring is performed, and after standing, pouring is performed to obtain the product.
[0013] As an embodiment of the present invention, in step S1, the carbon-based reinforcement phase includes any one of graphite, carbon fiber, carbon nanotube, and graphene. In some embodiments, the premixing is performed using a three-dimensional mixer.
[0014] Preferably, the at least two carbon-based reinforcement phases are graphite and carbon fiber.
[0015] As an embodiment of the present invention, in step S1, the total volume fraction of the carbon reinforcement phase in the metal material is 5%-20%. When the volume fraction of the carbon reinforcement phase is lower than 5%, the content of the reinforcement phase is small, and the thermal conductivity enhancement effect is poor; when the volume fraction of the carbon reinforcement phase is higher than 20%, the content of the reinforcement phase is too much, the viscosity of the composite material melt is too large, and the fluidity is significantly reduced, resulting in the formation of a large number of macroscopic pores and cracks after solidification, and the composite material is difficult to form. The preferred total volume fraction is 10%.
[0016] Furthermore, when there are two carbon-based reinforcement phases, the volume ratio is 1:1-1:4.
[0017] As an embodiment of the present invention, in step S1, the premixing speed is 30-100 rpm, and the mixing time is 15-45 min. In order to obtain as many pre-connected structures as possible, the mixing speed is preferably 50 rpm, and the mixing time is preferably 30 min.
[0018] As an embodiment of the present invention, in step S2, the matrix alloy includes any one of magnesium alloy, aluminum alloy and zinc alloy. In some embodiments, the smelting is carried out in a crucible, the pre-connected carbon reinforcement phase is laid on the bottom of the crucible, and then the matrix alloy is added therein.
[0019] As an embodiment of the present invention, in step S3, the melt temperature is cooled to 1-10°C above the liquidus temperature of the matrix alloy. If the stirring start temperature is too low, the alloy melt is easy to solidify, and the stirring paddle is subject to greater resistance and is difficult to start; if the stirring start temperature is too high, the magnesium alloy is easy to induce air entrainment, resulting in a large amount of magnesium oxide inclusions and deteriorating the thermal conductivity of the composite material. Therefore, the stirring start temperature is preferably 5°C above the liquidus of the matrix material.
[0020] As an embodiment of the present invention, in step S3, the stirring speed is 50-300 rpm and the time is 5-15 min. If the stirring speed is too low or the stirring time is too short, it is difficult to start floating as many reinforcement phase particles pre-laid on the bottom of the crucible as possible, which significantly reduces the yield of the reinforcement phase; if the stirring speed is too high or the stirring time is too long, it is easy to cause air entrainment, so the preferred stirring speed is 250 rpm and the preferred stirring time is 10 min.
[0021] As an embodiment of the present invention, in step S3, the standing time is 1-40 seconds. The shorter the time, the more conducive it is to reducing the sedimentation of the reinforcement phase.
[0022] In a second aspect, the present invention provides a metal material having a continuous network thermal conductive structure obtained by the preparation method.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention constructs a continuous network thermal conductive structure by utilizing premixed powder and pre-spreading powder stirring casting process; on the one hand, the heat flow can be continuously and efficiently conducted along the structure, giving full play to the thermal conductivity potential of the anisotropic carbon reinforcement phase; on the other hand, the probability of electron scattering in a low thermal conductivity matrix is reduced. Therefore, compared with the conventional stirring casting process, the metal-based material prepared by the premixed powder and pre-spreading powder stirring casting process has a higher thermal conductivity coefficient, which solves the problem that it is difficult to construct a continuous network thermal conductive structure by the conventional stirring casting process.
[0025] 2. On the one hand, the present invention optimizes the rotation speed and time of the premixed powder to increase the number of pre-connections formed, which is beneficial to the construction of a continuous network thermal conductive structure; on the other hand, by optimizing the type selection of carbon-based reinforcing phases, the rotation speed difference between heterogeneous reinforcing phase particles is increased, which is beneficial to the construction of a continuous network thermal conductive structure, thereby synergistically improving the thermal conductivity of metal materials; at the same time, a theoretical model of the critical speed of reinforcing phase particles based on premixed powder and pre-powder stirring casting process is proposed, which can be used to describe the flow behavior of particles in the melt and guide the design of actual process parameters.
[0026] 3. The present invention retains the advantages of stirring casting, such as simplicity, low cost, and the ability to form complex parts in one go, and is suitable for industrial production. At the same time, it retains the practicality and economic advantages of the stirring casting process, and can form complex parts in one go and is suitable for industrial batch continuous production.
[0027] 4. Compared with metal-based materials prepared by processes such as powder metallurgy + deformation, the metal-based materials with continuous mesh thermal conductive structure prepared by the present invention have isotropic thermal conductivity, which is beneficial to the comprehensive heat dissipation performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0029] Figure 1 The three stages of the flow behavior of reinforcement phase particles in the stirred melt in the premixed powder and pre-spread powder stirring casting process: Ⅰ particle floating, Ⅱ horizontal rotation and Ⅲ sedimentation stage;
[0030] Figure 2 is the stress of the reinforcement phase particles in the stirred melt; where F s is shear force, G is gravity, F f is the buoyancy, F v is the viscous force generated by the vertical movement of particles in the melt, F v ' is the viscous force generated by the horizontal movement of particles in the melt;
[0031] Figure 3 The carbon fiber / graphite connection structure formed by the premixed powder in Example 1;
[0032] Figure 4 is the quantitative relationship between the critical speed of carbon fiber / graphite and the distance from the particle to the center of the stirring paddle in Example 1;
[0033] Figure 5 The microstructure of the composite material prepared in Example 1 and Comparative Examples 1, 2, and 3;
[0034] Figure 6 The three-dimensional morphology and cross-sectional view of the composite material prepared in Example 1. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.
[0036] In order to clarify the technical principle of premixed powder and pre-spread powder stir casting to construct a continuous network thermal conductive structure, the following theoretical analysis is made. Under the stir casting process, the distribution of reinforcement phase particles in the metal matrix is mainly determined by their movement during melt stirring and solidification, which correspond to the flow behavior and solidification behavior of reinforcement phase particles, respectively.
[0037] The flow behavior of reinforcement phase particles in the stirred melt can be divided into three stages: particle floating, horizontal rotation and sedimentation (see Figure 1 ). The flow behavior of particles is determined by the forces acting on them. According to multiphase fluid mechanics, the forces acting on particles include the shear force F generated by stirring. s , gravity G, buoyancy F f and the viscous force F generated by the movement of particles in the melt v ( Figure 2 ), and its corresponding calculation formula is as follows:
[0038]
[0039] F f =ρ m gV (2)
[0040] G=ρ p gV (3)
[0041] F v =F′ v =6πrvη (4)
[0042] Among them, F I (N) represents the inertial force generated by stirring, m(g) represents the mass of the particles, ω p (rad / s) represents the angular velocity of the particle, R (m) represents the distance from the particle to the center of the stirring blade, ρ m and ρ p (kg / m 3 ) represent the density of melt and particles, g (m / s 2 ) represents the acceleration due to gravity, V(m 3 ) represents the particle volume, r (m) represents the particle radius, v (m / s) represents the particle velocity, and η (Pa·s) represents the dynamic viscosity of the melt.
[0043] Through force analysis and theoretical derivation, a theoretical model of critical speed of reinforcement phase particles can be obtained to guide actual process design:
[0044]
[0045] Where n represents the critical speed of the particles and θ represents the angle of the stirring paddle.
[0046] According to Equation 5, the critical speed n of the particle depends on the particle density ρ p , melt density ρ m , the distance R from the particle to the center of the stirring blade and the blade angle θ. Particle density ρ p The larger the distance R is, the larger the critical speed n is required. When the particles are constant, the critical speed n decreases as the distance R increases. When R approaches zero, the critical speed n approaches infinity, and a non-moving zone appears near the stirring blade. According to formula 5, the quantitative relationship between the particle speed n and the distance R can be expressed. At the same time, the speed relationship of heterogeneous particles A and B can also be derived:
[0047]
[0048] First, the pre-connected structure between the reinforcing phase particles can be formed through the pre-mixed powder process, which is conducive to the construction of a continuous network thermal conductive structure. In addition, Equation 6 shows that the density difference between the heterogeneous particles and the density difference between each particle and the metal melt simultaneously lead to the rotation speed difference between the heterogeneous particles. Although the pre-connected structure of some reinforcing phase particles may be separated due to stirring, the rotation speed difference between the heterogeneous particles promotes their meeting, thereby increasing the probability of forming a continuous network thermal conductive structure. The more pre-connections formed by the pre-mixed powder; the greater the density difference between the heterogeneous reinforcing phase particles, the greater the density difference between each reinforcing phase particle and the metal melt, resulting in a greater rotation speed difference between the heterogeneous reinforcing phase particles, and the more conducive to the construction of a continuous network thermal conductive structure.
[0049] The sedimentation of the reinforcement phase is a common problem in the stirring casting process, which will greatly reduce the recovery rate of the reinforcement phase particles. The faster the speed before the stirring stops, the greater the initial kinetic energy of the particles, and the easier it is to cause sedimentation. Therefore, in order to reduce particle sedimentation, it should be ensured that the casting is performed within a certain period of time after the stirring stops.
[0050] As for the solidification behavior of the reinforcement phase particles, when the composite melt solidifies, the advancing solid-liquid interface front meets the reinforcement phase particles. Due to the high thermal conductivity of the reinforcement phase particles, the reinforcement phase particles can accelerate the heat flow from the melt to the solid-liquid interface front, forming a concave interface, and then being swallowed by the interface and entering the interior of the grain. Since there is no particle redistribution during solidification, the swallowing mechanism of high thermal conductivity particles ensures the retention of a continuous network thermal conductive structure.
[0051] Example 1
[0052] Pure magnesium is used as the matrix (its thermal conductivity is 156W / (m·K) after testing), and a premixed powder and pre-spread powder stirring casting process is adopted. 5vol.% carbon fiber (CF) and 5vol.% graphite (GF) are added to construct a continuous network thermal conductive structure, which specifically includes the following steps:
[0053] S1. Premixed powder: premix carbon fiber and graphite using a three-dimensional mixer, the mixing speed of the three-dimensional mixer is 50 rpm, the mixing time is 30 min, and the mixture is formed as follows Figure 3 The carbon fiber / graphite pre-connected structure shown;
[0054] S2, pre-paving powder: laying the carbon fiber / graphite forming a pre-connected structure on the bottom of the crucible;
[0055] S3, smelting: add 2kg of pure magnesium into the crucible, and then start heating and smelting;
[0056] S4, liquid stirring: after pure magnesium is melted, when the temperature of the melt is cooled and stabilized to 5°C above the melting point of pure magnesium (655°C), mechanical stirring is started, the mechanical stirring speed is 250r / min, and the mechanical stirring time is 10min;
[0057] S5. Pouring: To reduce particle sedimentation, pouring is performed within 40 seconds after stirring stops to obtain a metal material with a continuous network thermal conductive structure.
[0058] According to the theoretical model of the critical speed of the reinforcement phase particles (Equation 5), the quantitative relationship between the critical speed of carbon fiber / graphite and the distance from the particle to the center of the stirring paddle can be obtained ( Figure 4 ), which can be used to guide the design of actual process parameters (such as stirring speed). When the particle speed exceeds 250rpm, it can ensure that more than 98% of carbon fiber and more than 94% of graphite start and smoothly enter the second stage of horizontal rotation. In addition, the critical speed relationship of CF / GF in the second stage is shown in Equation 7, indicating that there is a speed difference between the two.
[0059]
[0060] The carbon fiber / graphite pre-connected structure formed by the premixed powder and the horizontal rotation speed difference of the carbon fiber / graphite promote the construction of a continuous network thermal conductive structure. The microstructure and three-dimensional morphology of the magnesium-based material are shown in Figure 5 ab and Figure 6 As shown in the figure, a continuous network thermal conductive structure was successfully constructed. Samples were taken from the bottom of the magnesium-based material to test its thermal conductivity.
[0061] Example 2
[0062] The preparation method of this embodiment is basically the same as that of embodiment 1, except that the carbon fibers are replaced by carbon nanotubes.
[0063] Example 3
[0064] The preparation method of this embodiment is basically the same as that of Embodiment 1, except that graphite is replaced by graphene.
[0065] Comparative Example 1
[0066] Using pure magnesium as the matrix, a conventional stirring casting process is used to add a total of 5 vol.% carbon fiber and 5 vol.% graphite in small amounts and gradually, specifically including the following steps:
[0067] S1. Melting: Add 2 kg of pure magnesium into a crucible and then start heating and melting;
[0068] S2, feeding: after pure magnesium is melted, when the temperature of the melt is cooled and stabilized to 5°C above the melting point of pure magnesium (655°C), mechanical stirring is started at a speed of 250r / min, and a total of 5 vol.% carbon fiber and 5 vol.% graphite are added in small amounts and gradually in the vortex generated by stirring. The entire mechanical stirring and feeding process lasts for 30 minutes;
[0069] S3. Pouring: To reduce particle sedimentation, pour within 40 seconds after stirring stops.
[0070] The microstructure of the magnesium-based material is Figure 5 As shown in Figure cd, carbon fiber and graphite are evenly and randomly distributed, and due to the long-term high-speed stirring during the feeding process, a small amount of inclusions appear in the magnesium-based material due to air entrainment. Samples are taken from the bottom of the magnesium-based material to test its thermal conductivity.
[0071] Comparative Example 2
[0072] Using pure magnesium as the matrix, a pre-powder stirring casting process is adopted to directly lay 5 vol.% carbon fiber and 5 vol.% graphite on the bottom of the crucible (without pre-mixing powder process), which specifically includes the following steps:
[0073] S1, pre-powdering: 5 vol.% carbon fiber and 5 vol.% graphite are spread on the bottom of the crucible;
[0074] S2, smelting: add 2kg of pure magnesium into the crucible, and then start heating and smelting;
[0075] S3, liquid stirring: after pure magnesium is melted, when the temperature of the melt is cooled and stabilized to 5°C above the melting point of pure magnesium (655°C), mechanical stirring is started, the mechanical stirring speed is 250r / min, and the mechanical stirring time is 10min;
[0076] S4. Pouring: To reduce particle sedimentation, pour within 40 seconds after stirring stops.
[0077] The microstructure of the magnesium-based material is Figure 5 As shown in Fig. ef, a small amount of local connection between carbon fiber and graphite occurs, but the overall effect is weaker than that of Example 1 (premixed powder and pre-spreading powder stirring casting process). Samples were taken from the bottom of the magnesium-based material to test its thermal conductivity.
[0078] Comparative Example 3
[0079] Using pure magnesium as the matrix, a semi-pre-powder stirring casting process is adopted, that is, 5 vol.% carbon fiber is pre-laid, and 5 vol.% graphite is added in small amounts and gradually during stirring, which specifically includes the following steps:
[0080] S1, pre-powdering: 5 vol.% carbon fiber is spread on the bottom of the crucible;
[0081] S2, smelting: add 2kg of pure magnesium into the crucible, and then start heating and smelting;
[0082] S3, liquid stirring: after pure magnesium is melted, when the temperature of the melt is cooled and stabilized to 5°C above the melting point of pure magnesium (655°C), mechanical stirring is started at a speed of 250r / min, and 5vol.% graphite is added to the vortex generated by the stirring. The duration of the entire mechanical stirring process is 15min;
[0083] S4. Pouring: To reduce particle sedimentation, pour within 40 seconds after stirring stops.
[0084] The microstructure of the magnesium-based material is Figure 5 As shown in Figure gh, carbon fiber and graphite are partially connected, but still less than that in Example 1 (premixed powder and pre-spreading powder stirring casting process). Samples were taken from the bottom of the magnesium-based material to test its thermal conductivity.
[0085] Comparative Example 4
[0086] The preparation method of this comparative example is basically the same as that of Example 1, except that in step S1, the mixing speed is 10 rpm and the mixing time is 10 min.
[0087] Comparative Example 5
[0088] The preparation method of this comparative example is basically the same as that of Example 1, except that in step S1, the mixing speed is 150 rpm and the mixing time is 60 min.
[0089] Performance Testing
[0090] Test method: Test the thermal conductivity (thermal conductivity) of the material at room temperature (25°C). Use a laser transient thermal conductivity meter (LFA467) to test the thermal diffusivity α, and use the DSC three-step method to test the specific heat capacity C. p The density ρ is measured by an electronic density meter (ET-320). The thermal conductivity λ is given by λ=ραC pThe test results are shown in Table 1.
[0091] Table 1 Thermal conductivity of magnesium-based materials in embodiments and comparative examples
[0092]
[0093]
[0094] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a metal material having a continuous network thermal conductive structure, characterized in that: The following steps are involved: S1, premixing at least two carbon-based reinforcement phases to form a pre-connection; S2, laying the pre-connected carbon reinforcement phase under the base alloy and melting it; S3, after the temperature of the melt after smelting is cooled to above the liquidus temperature of the matrix alloy, stirring is performed, and after standing, pouring is performed to obtain the product.
2. The preparation method according to claim 1, characterized in that: In step S1, the carbon reinforcement phase includes any one of graphite, carbon fiber, carbon nanotube, and graphene.
3. The preparation method according to claim 1, characterized in that: In step S1, the at least two carbon-based reinforcement phases are graphite and carbon fiber.
4. The preparation method according to claim 1, characterized in that: In step S1, the total volume fraction of the carbon-based reinforcement phase in the metal material is 5%-20%; when there are two types of the carbon-based reinforcement phase, the volume ratio is 1:1-1:
4.
5. The preparation method according to claim 1, characterized in that: In step S1, the premixing speed is 30-100 rpm, and the mixing time is 15-45 min.
6. The preparation method according to claim 1, characterized in that: In step S2, the base alloy includes any one of magnesium alloy, aluminum alloy and zinc alloy.
7. The preparation method according to claim 1, characterized in that: In step S3, the temperature of the melt is cooled to 1-10°C above the liquidus temperature of the matrix alloy.
8. The preparation method according to claim 1, characterized in that: In step S3, the stirring speed is 50-300 rpm and the time is 5-15 min.
9. The preparation method according to claim 1, characterized in that: In step S3, the standing time is 1-40s.
10. A metal material having a continuous network heat-conducting structure prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A kind of preparation method of graphite particle reinforced magnesium matrix composite material
CN103820670B
A low-cost preparation method for diamond-reinforced metal matrix composites with high thermal conductivity
CN112981205B
Preparation method of lightweight high-thermal-conductivity graphite flake reinforced magnesium-based composite material
CN116970832A
Preparation method of ultrahigh-heat-conduction diamond / graphene reinforced aluminum-based composite material
CN117867310A